CSR Disclosure Quality: The Impact of Stand-alone Reports, Assurances, Reporting Guidelines, and Stakeholders - Regita Nendya Arum; Dewi Amalia (Jurnal Reksa, 2022)
This study aims to investigate the effect of stand-alone reports, assurances, reporting guidelines, and stakeholders on corporate social responsibility disclosure (CSRD) quality. Secondary data related to the investigated variables were documented from the sustainability reports of manufacturing companies listed in the Indonesia Stock Exchange. Twenty-four companies were selected based on the purposive sampling method from 2018 to 2020, resulting in 72 firm-year data being investigated. The data were analyzed using multiple regression analysis. The analysis results show that reporting guidelines affect the quality of CSRD. Companies that follow the GRI reporting framework have high-quality CSRD. However, this study did not find the effect of stand-alone reports, assurances, and stakeholders on CSRD quality.